Asthma and rhinitis among Chinese children — Indoor and outdoor air pollution and indicators of socioeconomic status (SES). (June 2018) - Norbäck, Dan; Lu, Chan; Wang, Juan; Zhang, Yinping; Li, Baizhan; Zhao, Zhuohui; Huang, Chen; Zhang, Xin; Qian, Hua; Sun, Yuexia; Sundell, Jan; Deng, Qihong
Abstract: Background: Few data exist on asthma and rhinitis across China in relation to indoor and outdoor air pollution, climate and socioeconomic factors. The main aim was to study associations between asthma, rhinitis and current respiratory symptoms among pre-school children across China and selected indoor and outdoor exposure and indicators of socio-economic status (SES) in mutually adjusted models. Methods: Chinese children (3–6 yr.) (n = 39, 782) were recruited from randomly selected day care centres in seven cities in China. Data on asthma, respiratory symptoms, rhinitis, indoor and outdoor exposure at home and SES were assessed by a parentally administered questionnaire. Lifetime mean ambient temperature, PM10, NO2, and GDP per capita on city level were calculated. Results: Totally 7.4% had ever doctors' diagnosed (DD) asthma and 8.7% DD-rhinitis, 19.7% had current wheeze, 45.0% rhinitis and 16.9% cough. DD-asthma was associated with ambient temperature (OR = 1.15, 95% CI 1.11–1.20 per °C), NO2 (OR = 1.16, 95% CI 1.02–1.33 per 10 μg/m 3 ), indoor mould/dampness (OR = 1.25, 95% CI 1.13–1.39) and living near major roads (OR = 1.13, 95% CI 1.02–1.25). DD-rhinitis was associated with ambient temperature (OR = 1.07, 95% CI 1.05–1.10 per °C), NO2 (OR = 1.20, 95% CI 1.09–1.32 per 10 μg/m 3 ), GDP (OR = 1.03, 95% CI 1.01–1.06 per 10, 000 RenMinBi/year), indoor mould/dampness (OR = 1.23, 95% CI 1.11–1.35), passive smoking (OR = 1.11, 95% CI 1.01–1.21), and living near major roads (OR = 1.14, 95% CI 1.03–1.25). Children in suburban or rural areas, in larger families (≥5 persons) and with prenatal farm exposure had less DD-asthma and DD-rhinitis. Conclusions: Economic development level of the city, higher SES, ambient temperature, NO2, PM10, traffic air pollution and mould/dampness can be risk factors for asthma and rhinitis and respiratory symptoms among pre-school children in China. Breastfeeding, large family size and early-life farm exposure could be protective factors. Highlights: Passive smoking and mould or dampness can be risk factors for asthma and rhinitis. Traffic related air pollution (TRAP) can be a risk factor for asthma and rhinitis. Breastfeeding, large family size and early-life farm exposure can be protective. Urbanization can be linked to less wheeze but more rhinitis and diagnosed asthma.